Adaptation and Identity Negotiation Among Non-Muslim Students in Indonesian Islamic Higher Education - Hasan Asari; Sahkholid Nasution; Harun Al-Rasyid; Muhammad Rifqi Irsyad (Jurnal Pendidikan Islam, 2026)
State Islamic Higher Education (PTKIN) in Indonesia has transformed into inclusive higher education institutions that accommodate students from diverse religious backgrounds. However, the dominance of Islamic Studies within the curriculum presents unique academic and socio-cultural challenges for non-Muslim students, particularly in terms of comprehension, participation, and identity negotiation. This study aims to explore the adaptation strategies employed by non-Muslim students in engaging with Islamic Studies at PTKIN. A qualitative research design was adopted to capture in-depth experiences and perspectives. Data were collected through interviews and observations involving 18 participants, comprising 15 non-Muslim students and 3 university leaders. The data analysis followed a systematic process of categorization, interpretation, pattern identification, and naturalistic generalization. The findings reveal that non-Muslim students employ two main adaptation strategies: conformity and consistency. Conformity strategies include cognitive, affective, social, and learning adjustments that facilitate academic engagement. Meanwhile, consistency strategies enable students to maintain their personal religious beliefs while participating in Islamic learning environments. In conclusion, the study highlights the dynamic negotiation between adaptation and identity preservation among non-Muslim students. The findings imply that Islamic higher education institutions should foster inclusive pedagogical practices, supportive academic environments, and culturally responsive policies to enhance equity and participation in Islamic education.